The Impact of COVID-19 Pandemic on Costs of Custom-Made Devices Used for Advanced Endovascular Aneurysm Repair Procedures - Mahnaz Khomamizadeh BSc; Naomi Eisenberg PT; MEd; CCRP; Graham Roche-Nagle MD MBA (Canadian Journal of Business, Economics and Health Management, 2026)
Advanced endovascular aneurysm repair (AEVAR) using custom-made devices (CMDs) is a critical intervention for complex abdominal aortic aneurysms (AAAs). However, CMDs are among the costliest components of these procedures, and recent global inflation, exacerbated by the COVID-19 pandemic may be impacting their affordability and accessibility in Ontario, Canada. This study investigates CMD cost trends during the peri-COVID-19 pandemic period. A retrospective review was conducted on AEVAR procedures involving CMDs at a single academic hospital in Ontario from April 2018 to March 2023. CMD costs were tracked and analyzed by fiscal year, CMD type, and vendor. CMDs implanted in multiple fiscal years with complete cost data were included. Percent change in average annual cost was calculated to assess inflationary trends. Of 193 AEVAR cases, 125 CMDs met inclusion criteria. CMD costs peaked in FY 2020/21, the first full COVID-19 year, with continued increases in subsequent years. Compared to FY 2018/19, average CMD costs rose by 6.15% in FY 2020/21, 7.85% in FY 2021/22, and 9.54% in FY 2022/23. Despite policy updates to improve AEVAR funding, CMD cost increases persist and may be outpacing adjustments in provincial funding models. CMD costs for AEVAR procedures have risen notably since the onset of the COVID-19 pandemic, revealing ongoing medical inflation pressures. Current funding mechanisms may not sufficiently account for these rising costs, risking inequitable access and institutional budget strain. Policy revisions are needed to align funding models with the evolving cost landscape of advanced vascular care.